2010
DOI: 10.1590/s0037-86822010000400012
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous visceral leishmaniasis in Brasília, Federal District, Brazil

Abstract: Introduction: Visceral leishmaniasis is a public health threat in Brazil considering the high lethality rates and increasing geographical dispersion to large urban conglomerates over the past 25 years. This study aimed to confirm suspected autochthonous cases of visceral leishmaniasis The disease predominantly affected children (12/21) and those from the Sobradinho region (16/21); the typical presentation of fever, hepatosplenomegaly and pancytopenia was observed in 67% of cases. Three deaths occurred during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 14 publications
2
21
0
7
Order By: Relevance
“…In the present study, VL was more frequent in children aged 0-9 years, a similar result to that found in the literature 5,24,25 , although a change in this profile has been detected, with an increased number of cases in young adults 26,27 . The higher susceptibility of children is explained by their relative cellular immaturity, aggravated by the malnutrition usually found in endemic areas and even by higher exposure to the vector in the peridomicile 5 .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, VL was more frequent in children aged 0-9 years, a similar result to that found in the literature 5,24,25 , although a change in this profile has been detected, with an increased number of cases in young adults 26,27 . The higher susceptibility of children is explained by their relative cellular immaturity, aggravated by the malnutrition usually found in endemic areas and even by higher exposure to the vector in the peridomicile 5 .…”
Section: Discussionsupporting
confidence: 92%
“…Higher VL incidence in males, also observed in other studies [21][22][23] , may be indicative of higher exposure to risk-associated environments (while not ruling out the possibility of differences between genders in defense mechanisms against VL). This fact lends support to the hypothesis that infection is not limited to the household setting, as males and females are similarly distributed across urban regions.…”
Section: Ethical Considerationssupporting
confidence: 64%
“…In this way, the detection of synanthropic triatomines would be more efficient, thus reducing the chances of colonization of these insects in domiciliary units of DF. Other zoonoses transmitted by vectors in DF, such as visceral leishmaniasis 57 , also in the scope of epidemiological surveillance, call to attention investments in basic and applied research involving vector transmission in the region. In this sense, we bear in mind that American trypanosomiasis cannot be eradicated completely, the more likely scenario being a reduction in human infection risk with T. cruzi, especially from strategies of surveillance and vector control.…”
Section: Conflict Of Interest Financial Support Referencesmentioning
confidence: 99%